Dietary choline and betaine intake, choline-metabolising genetic polymorphisms and breast cancer risk: a case–control study in China. Issue 6 (4th August 2016) - Du, Yu-Feng; Luo, Wei-Ping; Lin, Fang-Yu; Lian, Zhen-Qiang; Mo, Xiong-Fei; Yan, Bo; Xu, Ming; Huang, Wu-Qing; Huang, Jing; Zhang, Cai-Xia
Abstract: Choline and betaine are essential nutrients involved in one-carbon metabolism and have been hypothesised to affect breast cancer risk. Functional polymorphisms in genes encoding choline-related one-carbon metabolism enzymes, including phosphatidylethanolamine N -methyltransferase ( PEMT ), choline dehydrogenase ( CHDH ) and betaine-homocysteine methyltransferase ( BHMT ), have important roles in choline metabolism and may thus interact with dietary choline and betaine intake to modify breast cancer risk. This study aimed to investigate the interactive effect of polymorphisms in PEMT, BHMT and CHDH genes with choline/betaine intake on breast cancer risk among Chinese women. This hospital-based case–control study consecutively recruited 570 cases with histologically confirmed breast cancer and 576 age-matched (5-year interval) controls. Choline and betaine intakes were assessed by a validated FFQ, and genotyping was conducted for PEMT rs7946, CHDH rs9001 and BHMT rs3733890. OR and 95 % CI were estimated using unconditional logistic regression. Compared with the highest quartile of choline intake, the lowest intake quartile showed a significant increased risk of breast cancer. The SNP PEMT rs7946, CHDH rs9001 and BHMT rs3733890 had no overall association with breast cancer, but a significant risk reduction was observed among postmenopausal women with AA genotype of BHMT rs3733890 (OR 0·49; 95 % CI 0·25, 0·98). Significant interactions were observed between choline intake and SNP PEMT rs7946 ( P interaction =0·029) and BHMT rs3733890 ( P interaction =0·006) in relation to breast cancer risk. Our results suggest that SNP PEMT rs7946 and BHMT rs3733890 may interact with choline intake on breast cancer risk.